A study on the effectiveness of training programs in improving biomedical waste handling in a tertiary care hospital, Bengaluru: A pre-post study - Darshan Shivashankarappa; Sweta Balappa Athani; Seema P; Chandana Hombaiah; Padmavathy M; Sharath BN (Elsevier, 2024)
Background: In addition to being centres for healing, hospitals are major producers of infectious waste. The current study was carried out at a 700-bed tertiary care hospital in Bengaluru to assess Biomedical Waste (BMW) management practices at the source of generation and to ascertain the efficacy of training on the knowledge, attitude, and practice (KAP) of healthcare workers (HCW). Methods: Before the structured training program, each participant filled out the pre-test questionnaire. The structured training program on BMW (M and H) rules was conducted using audiovisual learning techniques. Immediately after the end of the training session, participants were given the 1st post-test questionnaire. Three months after the training session, the participants were given the 2nd post-test questionnaire. Results: Out of 183 participants involved in the study, 33.9 % of the participants were males, while 66.1 % were females. Wilcoxon Signed Rank Test was applied to the pre-and post-interventional knowledge and practices. There was a significant mean difference between pre-interventional (4.7 ± 1.7) and post-interventional knowledge (post-test 1-8.8 ± 1.3; post-test 2-7.3 ± 1.4) regarding Bio-medical waste management. Similarly, a significant difference in mean between pre-interventional (5.9 ± 1.4) and post-interventional practices (post-test 1-8.6 ± 1.1; post-test 2-7.3 ± 1.2) regarding BMW management. Conclusion: The study concluded that regular training programs on BMW and its hazards for all HCWs including group D workers should be conducted.